EXPERIENCE OF INTRAMUSCULAR METHOTREXATE USE IN A PATIENT WITH EARLY POLYARTICULAR JUVENILE IDIOPATHIC ARTHRITIS - E. I. Alexeeva; T. V. Sleptsova; T. M. Bzarova; S. I. Valieva; R. V. Denisova; K. B. Isaeva; E. V. Mitenko; E. G. Chistyakova; A. M. Chomakhidze; A. N. Fetisova; O. L. Lomakina; N. I. Taybulatov (Педиатрическая фармакология)
This article presents a case of severe course of polyarticular juvenile idiopathic arthritis. Active articular syndrome, high laboratory parameters of disease activity, severe incompetence were observed in a child by the therapy initiation. Successful use of intramuscular methotrexate in the dose of 15 mg/m2 of body surface per week is described. Exudative articular alterations, arthralgiae, morning stiffness duration reduced as early as one month after the therapy initiation in a child. Acute inflammatory articular alterations cut off, range of motions recovered completely in 4 out of the 6 affected joints, laboratory parameters of disease activity reduced and normalized (ESR and CRP), inactive disease stage was registered after 6 months of treatment. We did not observe any undesirable phenomena in the setting of methotrexate therapy.